Feasibility Analysis of Red Dragon Fruit (Hylocereus polyrhizus) Farming in Rimbo Ilir District, Tebo Regency - Evo Afrianto; M. Ari Putra Pangestu; Isyaturriyadhah Isyaturriyadhah (Fakultas Pertanian Universitas Muara Bungo, 2021)
This study aims to analyze the level of income of red dragon fruit farming and the feasibility of red dragon fruit farming in Rimbo Ilir District, Tebo Regency. The research was conducted in Giriwinangun Village and Sumber Agung Village, Tebo Regency, which were chosen purposively with the consideration that these two villages have the largest land area and the highest number of milestones among other villages in Rimbo Ilir District. The research was conducted using the survey method, namely obtaining natural (not artificial) data by distributing questionnaires, tests and interviews. Withdrawal of sample farmers was carried out by proportional sampling of 15% of the Red Dragon Fruit RTP from Giriwinangun Village and Sumber Agung Village, Rimbo Ilir District, Tebo Regency, which amounted to 198 (RTP). Each from Giriwinangun Village is 112 (RTP) and Sumber Agung Village is 86 (RTP). So the number of samples in this study was 30 (RTP). The analysis used in this study is income analysis and feasibility analysis, namely NPV analysis, IRR analysis and Net B/C Ratio analysisThe results showed that the average income received by dragon fruit farmers for one year in the research area was Rp. 10,912,000, - with the average income of dragon fruit farming in the research area was Rp. 7,099.523, - per year. The resulting Net B/C value is 6.64 with a positive NPV value of Rp 28,437,364.76, - and an IRR of 43.90%. Where the Net B/C value 1, NPV value 1 and IRR value loan interest rate, it means that red dragon fruit farming in Rimbo Ilir District, Tebo Regency is feasible to be developed financially.